2016
DOI: 10.1152/japplphysiol.00727.2015
|View full text |Cite
|
Sign up to set email alerts
|

Liver kinase B1 inhibits the expression of inflammation-related genes postcontraction in skeletal muscle

Abstract: Skeletal muscle-specific liver kinase B1 (LKB1) knockout mice (skmLKB1-KO) exhibit elevated mitogen-activated protein kinase (MAPK) signaling after treadmill running. MAPK activation is also associated with inflammation-related signaling in skeletal muscle. Since exercise can induce muscle damage, and inflammation is a response triggered by damaged tissue, we therefore hypothesized that LKB1 plays an important role in dampening the inflammatory response to muscle contraction, and that this may be due in part t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It can not only exert the protective functions in antagonizing the inflammatory responses induced by mycobacterial infection, LPS or FGF21 24,27,29 , but also play critical roles in controlling the inflammation in T cells, cardiomyocyte, renal epithelial cilia, brown adipose tissue, skeleton muscle, etc. 25,26,28,30,31 . In the current study, we have provided the novel evidence that LKB1 was involved in mediating the proinflammatory responses in the bronchial epithelial cells upon PM2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It can not only exert the protective functions in antagonizing the inflammatory responses induced by mycobacterial infection, LPS or FGF21 24,27,29 , but also play critical roles in controlling the inflammation in T cells, cardiomyocyte, renal epithelial cilia, brown adipose tissue, skeleton muscle, etc. 25,26,28,30,31 . In the current study, we have provided the novel evidence that LKB1 was involved in mediating the proinflammatory responses in the bronchial epithelial cells upon PM2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous investigations have demonstrated that AMPK activity is reduced in skeletal muscle tissues of high-fat diet (HFD)-fed rats [17,18]. Liver kinase B1 (LKB1), a major upstream AMPK kinase, has been shown to promote mitochondrial biogenesis and antioxidative pathways in skeletal muscle after its activation [1921]. Protein kinase A (PKA), an upstream kinase in the LKB1/AMPK pathway [22], has been identified as a potential target for muscle wasting in several conditions [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports have identified increased inflammatory signaling upon Lkb1 loss in different cell and tissue contexts, such as in skeletal muscle (12), macrophages (13), T cells (14), and lung cancer (15), implicating Lkb1 as a suppressor of inflammatory pathways. In PJS patients and in Lkb1 +/-mice, inhibition of cyclooxygenase-2 with the selective inhibitor celecoxib demonstrated partial efficiency in reducing PJS polyposis by reducing the size but not the number of tumors (16).…”
Section: Introductionmentioning
confidence: 99%